Trapped by Fast Beauty Trapped by Fast Beauty: How Scarcity Promotion and Social Influence Drive Gen Z’s Impulse Buying - Pratiwi, Maria Indah; Ulya, Laila Listiana (Journal of Educational, Health and Community Psychology, 2025)
The growth of the cosmetics industry in Indonesia has led to the emergence of the fast beauty phenomenon, characterized by rapid production, low-cost ingredients, and aggressive promotion. This phenomenon has negative impacts, including the increasing tendency of online impulse buying, especially among Gen Z, the dominant users of e-commerce platforms. This study aimed to examine the influence of scarcity promotion and online social influence on online impulse buying of fast beauty products among Gen Z. A quantitative method was employed by distributing online questionnaires to 534 respondents, and the data were analyzed using IBM SPSS Statistics 23. The results showed that scarcity promotion had a significant positive effect on online impulse buying (β = 0.190, p < 0.05), while online social influence had a significant negative effect (β = -0.201, p < 0.05). Furthermore, both variables simultaneously had a significant effect on online impulse buying behavior (F = 30.959, p < 0.05). Contrary to expectations, the negative effect of online social influence may be explained by Gen Z’s tendency to critically evaluate online information before making purchase decisions. This research contributed to consumer psychology literature and provided practical insights for marketers in developing effective digital marketing strategies.